(untitled) (Ozone Therapy Global Journal, 2014)
Fibromyalgia is a disease of unknown ca use whose main sym ptom is chronic widesprea d musculos keletal pain accompanied by s ymptoms th at disrupt daily activities of patients. In this study the impact of ozone therapy in improving patients’ pai n and daily ac tivities to give them a bet ter quality of life was assessed. Clinical experience is described us i ng ozone t herapy in 30 wo me n aged 30 -65 years diagnosed with Fibromyalgia, Visual Analogue Scale (VAS) 6-9, with a time of disease progression between 1-10 years. Patients were treated with O2-O3 intramuscular with 10 sessions 2 times a week at doses o f 15 mg / mL, to gether were administered systemically 10 sessions 2 times a week alternating rectal insufflation and intravenous admi nistration of s aline 0.9% ozonated. The outcome of patients was continued by monitoring clinical symptoms and evaluation of the Visual Analogue Scale. The results showed an improvement in pain with 33% VAS 3-4 in the second week, improved sleep disorder in 46.6%, mood and daily activities by 40% and appreciated a decrease in the amount of drugs consumed by 30% of patients. The ozone therapy can be considered as an interesting as adjuva nt ther apy in the symptoms of fibromyalgia.